Detection of the Nav channel kdr-like mutation and modeling of factors affecting survivorship of Culex quinquefasciatus mosquitoes from six areas of Harris County (Houston), Texas, after permethrin field-cage tests. - Han-Jung Lee; Michael Longnecker; Travis L Calkins; Andrew D Renfro; Chris L Fredregill; Mustapha Debboun; Patricia V Pietrantonio (Public Library of Science (PLoS), 2020)
Culex quinquefasciatus is one of the most important mosquito vectors of arboviruses. Currently, the fastest approach to control disease transmission is the application of synthetic adulticide insecticides. However, in highly populated urban centers the development of insecticide resistance in mosquito populations could impair insecticide efficacy and therefore, disease control. To assess the effect of resistance on vector control, females of Cx. quinquefasciatus collected from six mosquito control operational areas in Harris County, Texas, were treated in field cage tests at three different distances with the pyrethroid Permanone® 31-66 applied at the operational rate. Females were analyzed by sequencing and/or diagnostic PCR using de novo designed primers for detecting the kdr-like mutation in the voltage-gated sodium channel (L982F; TTA to TTT) (house fly kdr canonical mutation L1014F). Females from the Cx. quinquefasciatus susceptible Sebring strain and those from the six operational areas placed at 30.4 m from the treatment source were killed in the tests, while 14% of field-collected mosquitoes survived at 60.8 m, and 35% at 91.2 m from the source. The diagnostic PCR had a with 97.5% accuracy to detect the kdr-like mutation. Pyrethroid resistant mosquitoes carrying the L982F mutation were broadly distributed in Harris County at high frequency. Among mosquitoes analyzed (n = 1,028), the kdr-kdr genotype was prevalent (81.2%), the kdr-s genotype was 18%, and s-s mosquitoes were less than 1% (n = 8). A logistic regression model estimated an equal probability of survival for the genotypes kdr-kdr and kdr-s in all areas analyzed. Altogether, our results point to a high-risk situation for the pyrethroid-based arboviral disease control in Harris County.